Coping with climate change: The role of spatial decision support tools in facilitating community adaptation. (June 2015) - Lieske, David J.
Abstract: Climate change challenges communities to visualize spatial patterns of risk, assess their vulnerability to those risks, and prepare adaptation plans to lower vulnerability. This paper outlines the design and implementation of a prototype web-based spatial decision support system (SDSS), referred to as the Community Adaptation Viewer (CAV), to assist adaptation planning. Thin-client, Javascript enabled web-SDSS software was constructed to allow interaction with urban infrastructure, and support "on-the-fly" assessment of social and economic vulnerability. Facilitated, decision-making workshops were conducted with small groups of stakeholders to evaluate the effectiveness of the prototype. The test case illustrates that high levels of information integration are practical to achieve, and that the SDSS can significantly enhance the ability of communities to conduct elaborate, geographically-specific climate change adaptation planning. Given the long time frame required to fulfil some adaptation plans, it is crucial that communities begin to develop and invest in adaptation strategies as soon as possible. Highlights: Evaluating climate change risks requires qualitative and quantitative information. This paper reports on the Community Adaptation Viewer (CAV) for adaptation planning. The CAV is an interactive web-based interface with feature creation tools. Users identify at-risk infrastructure and vulnerable community components. Supporting tools allow rapid assessment of economic and social vulnerability.